Determination of Training Material and Organisational Culture Impact in Vocational Training Effectiveness in Bahrain - Idrees Yaqoot, Ehsan Saeed; Mat, Norazuwa (Journal of Technical Education and Training, 2021)
The focus of this study is on vocational training programs effectiveness related antecedents at the public sector in Bahrain. The study employed the Kirkpatrick model as the framework of the research and evaluated the vocational training effectiveness as the dependent variable. The study explores the relationship that exists between the independent variables, training material, and organizational culture together with the training effectiveness. For data collection, a survey instrument was developed from 46 items distributed to the Bahraini public sector employees to test the two hypotheses. One hundred and twenty-eight (128 questionnaires were the usable obtained total. The quantitative method is the applied design analyzed by the SPSS statistic software package. The findings indicate a positive and significant relationship from both factors at Kirkpatrick's level of interest (result) and the training effectiveness. Also, unpredictably this study conquers a challenging and interesting area in the training setting for researchers in examining and optimizing the modality of training programmes. The study principally adds to the limited literature concerning vocational training effectiveness and training antecedents in the public sector. Effective training demands the organizations' administration and specialists to optimize the antecedents of training to achieve the organization's/training's objectives. Comprehending the consequence of these specific variables will assist the establishment to increase the training benefits and accordingly the human resources performance. Thus, these variables' importance should not be underestimated. The administration is supposed as well to take responsibility in promoting effective variables and drawing up an effective view.